Temporal processing abilities in normal hearing individuals with tinnitus: a systematic review - Puthiyadath, Malavika; Prabhu, Prashanth; Kalarikkal, Gayathri; Nisha, K. V. (Frontiers in Audiology and Otology, 2024)
Tinnitus, characterized by the perception of auditory phantoms, is prevalent worldwide and can lead to a range of hearing-related issues. Understanding its influence on temporal processing helps to delineate the auditory manifestations of tinnitus. This systematic review aimed to identify the patterns of temporal processing difficulties in individuals with tinnitus and normal hearing abilities. Furthermore, this review evaluates the potential of specific measurement techniques as tools for diagnosing temporal processing deficits in tinnitus. A comprehensive search was conducted in multiple international databases, followed by rigorous screening of the titles, abstracts, and full-length content. The inclusion and exclusion criteria were formulated using the Population, intervention, compression, Outcome, and Study design (PICOS) format, and the study bias was determined. After excluding irrelevant articles, nine studies were selected for the analysis. Over 50 % of the selected studies demonstrated a significant impact on temporal processing in individuals with tinnitus, especially with gap detection test (GDT) and gaps in noise (GIN) tests, indicating of the deficits in peripheral temporal process in tinnitus individuals with normal hearing. However, the other central auditory tests showed no major changes. The findings from this review underscore the importance of understanding temporal processing impairments in tinnitus and hold promise for enhancing the diagnostic accuracy and treatment outcomes, ultimately improving the lives of those affected by tinnitus. This review highlights the potential of the GDT and GIN tests as sensitive tools for assessing temporal processing deficits in the peripheral auditory system, which in turn can manifest as central changes in temporal processing.